The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1128/jvi.03275-13
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus A9 Infects Cells via Nonacidic Multivesicular Bodies

Abstract: Coxsackievirus A9 (CVA9) is a member of the human enterovirus B species in the Enterovirus genus of the family Picornaviridae. According to earlier studies, CVA9 binds to ␣V␤3 and ␣V␤6 integrins on the cell surface and utilizes ␤2-microglobulin, dynamin, and Arf6 for internalization. However, the structures utilized by the virus for internalization and uncoating are less well understood. We show here, based on electron microscopy, that CVA9 is found in multivesicular structures 2 h postinfection (p.i.). A neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 51 publications
5
44
0
Order By: Relevance
“…39,40 For both native viruses and virus-fluorescent probe conjugates, the number of infected cells increased rapidly after 6, 12 and 24 h. However, as observed with the other infectivity methods, the virus-fluorescent probe conjugates remained for a longer time in the vesicles before the start of replication. and later, virus replication is observed as the resulting high cytoplasmic accumulation of newly made capsid proteins.…”
Section: Gold Cluster and Fluorescent Dye Conjugates Bind To Virus Camentioning
confidence: 66%
“…39,40 For both native viruses and virus-fluorescent probe conjugates, the number of infected cells increased rapidly after 6, 12 and 24 h. However, as observed with the other infectivity methods, the virus-fluorescent probe conjugates remained for a longer time in the vesicles before the start of replication. and later, virus replication is observed as the resulting high cytoplasmic accumulation of newly made capsid proteins.…”
Section: Gold Cluster and Fluorescent Dye Conjugates Bind To Virus Camentioning
confidence: 66%
“…The results indicated that HCMV belongs to those viruses that can infect cells through an endocytic mechanism but do not require low pH to trigger penetration from the endocytic vacuoles. Others include HSV‐1, respiratory syncytial virus, Echovirus 1 and Coxsackievirus A9 . HCMV is unusual because low pH is required in endothelial and epithelial cells whereas no such requirement is observed in dendritic cells and fibroblasts .…”
Section: Discussionmentioning
confidence: 99%
“…Although, as reviewed by Moss (Moss B, 2012), the poxvirus entry fusion complex—composed of 11–12 glycosylated proteins—is abnormally complex, and other entry routes exist. Huttunem et al (2014) also implicate a Rac1-dependent entry mechanism, involving neutral multivesicular bodies, in Coxsackievirus A9 entry (Huttunen M, et al, 2014). Similarly, HSV-1 has been shown to utilize a RhoA, tyrosine kinase, and actin-dependent phagocytosis-like route for entry (Clement C, et al, 2006; Zheng K, et al, 2014 b ).…”
Section: Actin and Viral Entrymentioning
confidence: 99%